Effect of honey and calcium dips on quality of fresh-cut nectarine (Prunus persica L. Batsch) - Bo Wen; Xiaozhen Wu; Yaowapa Boon-Ek; Lan Xu; Haifa Pan; Peng Xu; Yuyue Wu; Suriyan Supapvanich (My University, 2018)
The effects of calcium chloride (CaCl2) and honey dips were investigated on the quality of fresh-cut nectarines. Nectarine fruit samples at the commercially ripe stage were wedged and then dipped in distilled water, 50% honey, 1% CaCl2 or 1% CaCl2 combined with 50% honey solutions, followed by storage at 4 ± 0.5 °C and 90 ± 2% relative humidity for 7 d. The following parameters were investigated during storage: firmness, total soluble solids (TSS), superficial color, color darkening score and index, total phenols content and the enzyme activities of peroxidase and polyphenol oxidase (PPO). CaCl2 and CaCl2 + honey solution dips improved the texture and maintained the TSS content. Honey and CaCl2 + honey suppressed an increase in the color difference. Minor changes were found in color attributes (lightness (L*), hue and chroma values), color darkening, total phenols content and PPO activity during storage. CaCl2 + honey maintained the quality of the nectarines by delaying color change and firmness loss.
Keywords: Lightness; Hue; Distilled water; Color difference; Postharvest Quality and Shelf Life Management